Granito Los Chilenos: Una nueva unidad granítica jurásica en Cerro Colorado, Sierras Australes de Buenos Aires. Implicancias tectónicas - Massabie, A.C. (1999)
Los Chilenos granite: a new Jurassic granite unit in Cerro Colorado, Sierras Australes de Buenos Aires. Tectonic implication. The Sierras Australes of Buenos Aires are located in the south-west corner of the Province about 100 km west of Bahia Blanca. On the south-west flank of these hills, younger Palaeozoic sedimentary formations overlie poorly exposed granitic and volcanic basement rocks. Granitic Cerro Colorado outcrops, located 16 km strike to the south of the town of San Martin de Tours, and near Lago Los Chilenos, have been included in this broadly interpreted "basement" in many previous geological studies. This contribution is mainly based on detailed structural mapping of the cerro Colorado area, and systematic sampling of granitic and sedimentary rocks for petrographical, microtectonic and Rb/Sr isotopic age analysis. In contrast to previous studies, two Phanerozoic granitic units have been recognised and mapped in the cerro Colorado area of Sierras Australes. The older one, the Cerro Colorado Granite (CC), is composed of foliated and sheared anisotropic granitic rocks with a Rb/Sr isochron age of 381±9 Ma (ir= 0.7035). The younger one, Los Chilenos Granite (LCh), consists of isotropic granophiric microgranite with a Rb/Sr isochron age of 140 ± 14 Ma (ir= 0.7126). This granite has intrusive contacts with both, the folded quartzite of the Mascota Formation and Cerro Colorado Granite (CC).The older tectomagmatic event (CC) is correlated with the compressive Chañica Orogeny, which was associated in the Sierras Australes region, with the eruption of La Mascota - La Hermita rhyolites (360±21 Ma) and the unconformity between Lolén Formation (Middle Devonian) and Sauce Grande Formation (Carboniferous).The younger intrusive event of Los Chilenos Granite (LCh) is considered to be associated with an extensional tectonic regime during the Late Jurassic initial rifting of the Atlantic Ocean. © 1999 Asociación Geológica Argentina.